Comparison of candidate scaffolds for tissue engineering for stress urinary incontinence and pelvic organ prolapse repair. (14th June 2013) - Mangera, Altaf; Bullock, Anthony J.; Roman, Sabiniano; Chapple, Christopher R.; MacNeil, Sheila
Abstract : Objectives: To identify candidate materials which have sufficient potential to be taken forward for an in vivo tissue‐engineering approach to restoring the tissue structure of the pelvic floor in women with stress urinary incontinence (SUI) or pelvic organ prolapse (POP). Materials and Methods: Oral mucosal fibroblasts were seeded onto seven different scaffold materials, AlloDerm ( LifeCell Corp., Branchburg, NJ, USA), cadaveric dermis, porcine dermis, polypropylene, sheep forestomach, porcine small intestinal submucosa (SIS) and thermoannealed poly(L) lactic acid (PLA) under both free and restrained conditions. The scaffolds were assessed for: cell attachment using AlamarBlue and 4, 6‐diamidino‐2phenylindole (DAPI); contraction using serial photographs; and extracellular matrix production using Sirius red staining, immunostaining and scanning electron microscopy. Finally the biomechanical properties of all the scaffolds were assessed. Results: Of the seven, there were two biodegradable scaffolds, synthetic PLA and natural SIS, which supported good cell attachment and proliferation. Immunostaining confirmed the presence of collagen I, III and elastin which was highest in SIS and PLA. The mechanical properties of PLA were closest to native tissue with an ultimate tensile strength of 0.72 ± 0.18 MPa, ultimate tensile strain 0.53 ± 0.16 and Young's modulus 4.5 ± 2.9 MPa. Scaffold restraint did not have a significant impact on the above properties in the best scaffolds. Conclusion: These data support both PLA and SIS as good candidate materials for use in making a tissue‐engineered repair material for SUI or POP.